Generation of atmospheric boundary layer in the IIUM low speed wind tunnel - Za’aba, Khalid Aldin; Asrar, Waqar; Aldheeb, Mohammad (IOP Publishing, 2017)
The purpose of this paper is to describe an attempt made to simulate the atmospheric boundary layer (ABL) in the Low Speed Wind Tunnel (LSWT) at IIUM. This was performed through modifications of the inlet and surface conditions of the test section. Devices such as spires, fences and surface roughness were used. The ASCE 7-10 standard was used as a reference to validate the results between the wind tunnel data and the full-scale ABL flow characteristics. The velocity profile and turbulence intensity were measured using a onedimensional hotwire (CTA) probe. The data obtained show good agreement with ASCE 7-10 velocity profiles for exposures B and C while using a scale of 1:488 to match the wind tunnel data. The turbulence intensity profiles do not show a good agreement.